Nilai-Nilai Karakter Religius dalam Novel “Negeri 5 Menara” Karya Ahmad Fuadi - Saraswati Saraswati (SOCIETIES: Journal of Social Sciences and Humanities, 2022)
Abstract. This study aims to (1) describe the values of spiritual religious characters in the novel "Negeri 5 Menara by Ahmad Fuadi", (2) describe the values of humanist religious characters in the novel "Negeri 5 Menara by Ahmad Fuadi", (3) describe the values of naturalist religious characters in the novel "Negeri 5 Menara by Ahmad Fuadi". This type of research is a type of descriptive qualitative research. This research was conducted by reading the entire contents of the novel Negeri 5 Menara by Ahmad Fuadi. The focus of this research is (1) the value of spiritual religious character, (2) the value of humanist religious character, and (3) the value of naturalist religious character. The data source of this research is obtained from the novel Negeri 5 Menara by Ahmad Fuadi in the form of a sentence that contains: (1) spiritual religious character values in human relations with God, (2) humanist religious character values in human relations with humans, (3) the values of naturalist religious character in human relations with their environment. Data collection techniques in this study were carried out by reading and recording techniques. The research instrument consists of the main instrument, namely the researcher himself and supporting instruments such as highlighters and cellphones for documentation. The results of the study show that: (1) The value of spiritual religious characters in the novel Negeri 5 Menara by Ahmad Fuadi instills the value of spiritual religious characters from every event experienced by each character which further adds to his closeness to his God. The spiritual religious character values include: Obedience, faith (trust), gratitude, repentance, and trust. (2) The value of humanist religious character instills the value of humanist character that occurs because of the process of interaction with himself and other humans. The values of the humanist religious character include: devoted, confident, helpful, responsible, not easy to give up, sincere, obedient to the rules, spacious, brave, diligent, mutual respect, mutual love, tolerance and independence. (3) The value of humanist religious character instills the value of a naturalist religious character in each character based on the awareness of the character's love for his environment. The values of the humanist religious character include: caring for environmental cleanliness and caring for environmental safety. Keywords: Values, Religious Character, Spiritual, Humanist, Naturalist.